Comparation Of Corruption Handling Between Indonesia And Malaysia - Mu'adi, Sholih (The journal of contemporary issues in business and government, 2021)
The purpose of this research is to make a comparison of political policies carried out by special institutions established by the governments of each country in the prevention and handling of corruption, so that the two countries can provide mutual input for the implementation of corruption handling activities in their respective countries based on statutory regulations. invitation that has existed to enhance the integrity of the country. The focus of the research is the policies of the Indonesian and Malaysian governments in the prevention of corruption eradication in their respective countries. Data collection is done by processing primary data, namely data that is carried out directly by the researcher through surveys, observation and documentation, while secondary data is carried out by researchers through magazines, newspapers, literature study whose function is to strengthen data in the previous year, either printed or electronic, so that the data can be summarized comprehensively in the required analysis. Data sources were obtained from the Corruption Eradication Commission (CEC), Malaysian Anti-Corruption Commission (MACC), and Indonesian Academics and Malaysian Academics. This research uses a qualitative approach. The results of this research are that in Indonesia, a complicated bureaucratic level between local and central government, the APIP (Government Internal Supervisory Apparatus) was formed, which is an organizational unit within the central government, local governments, State ministries, State institutions and non-governmental organizations. departments that have duties and functions to supervise within the scope of authority through auditing, reviewing, evaluating, monitoring, and other supervisory activities on the implementation of organizational duties and functions. This makes the level of prevention more complicated. Whereas in Malaysia the level of bureaucracy is simpler than Malaysia so that by establishing Corruption Risk Management (CRM): Corruption Risk Management (CRM), it is faster to take preventive measures against corruption. CRM is a management process designed to assist any organization in identifying structural weaknesses that could lead to corruption.